Revolution and Regeneration Life Cycle and the Historical Vision of the Generation of 1776 - Moran, Gerald (Georgia Open History Library, 1983)
Revolution and Regeneration is a book about the aging of the "young men of 1776," the men who came to adulthood with the American Revolution, found their identity merged with the new republic they had created, and grew old as the nation matured. As they identified themselves with their nation's past, so they used that past to judge their own lives and what they had accomplished, or failed to accomplish. Revolution and Regeneration is a marriage of psychohistory and intellectual history, applying the principles of the psychology of maturation to a generation whose experiences were crucial to our history-the generation of Adams, Jefferson, Hamilton, and Madison. Their need for identity drove them to demand independence for themselves and their communities. Revolution and Regeneration tells their stories, from youth to old age. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.